Dental caries and its association with present day dietary patterns: a cross-sectional study - Munjal, Vaibhav; Talwar, Puneet Singh; Singh, Jagjit; Kumar, Mandeep; Gambhir, Ramandeep (International Journal Of Community Medicine And Public Health, 2018)
Background: Dental caries is a multifactorial disease with diet being one of the contributing factors. The influence of vegetarianism on the development of caries has scarcely been investigated in the past. Therefore, this study was done to evaluate the association of dental caries with frequency of sugar exposures and vegetarian / mixed diet. Methods: The present cross-sectional study was conducted among 2500 school children of 12 and 15 years age groups selected on the basis of simple random sampling from different schools of the city. Dental caries was recorded using Decayed, Missing and Filled teeth index (WHO modification, 1997) and correlated with the different dietary variables. Subjects were also segregated on the basis of diet: vegetarian and mixed. Statistical analysis was done using Student t-test and Pearson’s Correlation Coefficient. Results: The prevalence of dental caries in the 12 and 15 year age group of subjects consuming mixed diet was 83.36% and 86.47% respectively. It was lower in case of subjects on vegetarian diet. The correlation between DMFS and TSE, FSE and AMSE was found to be statistically significant (p<0.05) in the 12 year age-group. In the 15 year age-group the correlation of DMFS with TSE and LSE was also found to be statistically significant (p<0.05). Conclusions: There was no statistically significant difference in dental caries status among subjects in both the groups (vegetarian and mixed). However, there was significant association between sugar exposures and dental caries among subjects of both the age-groups.